Investigation of Perceived Business Environment among MSMEs in Hungary with a Focus on Digitalization - Bujáki, János (Acta Carolus Robertus, 2024)
SMEs are under-researched in Europe, micro-sized enterprises are often even ignored in surveys. However, their contribution to GDP, employment, and balance of trade is beyond all dispute. A qualitative research has been conducted among micro, small, and medium-sized enterprises (MSMEs). Informants involved in the research were owner managers of companies various in terms of profile, age, and location within Hungary. Interviewed entrepreneurs named some common difficulties and hindering factors, as well as few specific trends supporting their business. Their perception of business environment, practice of planning, access to external funds, and level of digital readiness have been investigated. Outcomes of the study demonstrated the value of face to face semi-structured interviews with Informants of confidential relationship as well as served additional objective with the research, that is, to better establish and design a future quantative study. This paper was also aimed to contribute to the SME/MSME research in Europe due to their significance in national economies detailed in the study. Findings are partially in line with those of previous studies in international literature.